The Greek tragedy - Beckert, Jens,Arndt, H. Lukas R. (Max Planck Institute for the Study of Societies, 2024)
Between 2009 and 2015 Greece underwent a profound sovereign debt crisis that led to a serious political crisis in Europe and the restructuring of Greek debt. We argue that the prevalence of negative narratives about the future contributed to the changes in spreads of Greek bonds during the crisis. We support our argument by presenting results from text mining a corpus of 9,435 articles from the Financial Times and the Wall Street Journal. Based on sentiments and a machine learning model predicting future reference, we identify newspaper articles which generate negative and uncertain outlooks for the future in the expert discourse. We provide evidence from time series regression analysis showing that these negative imagined futures have explanatory power in models estimating spread development of Greek vs. German sovereign bonds. We suggest that these findings provide good evidence for the relevance of
21.11116/0000-000F-60D9-0
Keywords: Graue Literatur; bond spreads; economic sociology; financial markets; Greek debt crisis; imagined futures; sentiment analysis; sovereign debt; valuation; Anleihen-Spreads; Bewertung; Finanzmärkte; griechische Schuldenkrise; imaginierte Zukünfte; Staatsverschuldung; Sentimentanalyse; Wirtschaftssoziologie